Case Report: Durable complete pathologic response and organ preservation following ipilimumab and nivolumab for locally advanced primary vaginal mucosal melanoma - Tarhini, Ahmad A.; Hanayneh, Wissam B.; Powers, John J.; Segura, Carlos M. Moran; Conejo-Garcia, Jose R.; Lam, Cesar A.; Hakam, Ardeshir; Hoffman, Mitchel S. (Frontiers in Oncology, 2022)
Optimal management of locally advanced vaginal mucosal melanoma is poorly understood because of its rarity and unique biology. Patients have a poor prognosis despite aggressive management approaches including pelvic exenteration and adjuvant radiation that carry major morbidities. We report a case of a patient in early 40’s who experienced complete pathologic response and organ preservation following immunotherapy consisting of 3 cycles of ipilimumab and nivolumab. Treatment was complicated by a high-grade immune mediated hepatitis that eventually resolved with immunosuppressive therapy. Immune monitoring studies utilizing vaginal tumor biopsies showed evidence of enhanced infiltration by CD3+/CD8+ cytotoxic T-cells and increased expression of MHC-I/PD-L1 within the tumor microenvironment following immunotherapy. The patient continues to be without evidence of disease recurrence by radiologic and gynecologic examinations with more than 2 years of follow up from the time of immunotherapy initiation. To our knowledge, this is the only case report in the literature of a patient with locally advanced vaginal mucosal melanoma experiencing a durable complete pathologic response and organ preservation following immune checkpoint blockade as the only treatment approach.